BOTTOM WALL CONSTRUCTION OF “JODANG” TRAP APPLIED SELECTIVELY TO BABYLON TIGER (Babylonia spirata) SNAIL SIZE - Gondo Puspito; Agus Suherman (JOURNAL OF COASTAL DEVELOPMENT, 2012)
The objective of this research was to obtain net mesh bottom wall construction of “jodang” trap that selective to babylon tiger snails size, i.e. only shell length of l < 4.27 cm approximately could pass through. There were 3 designs shapes of bottom wall construction tested, i.e. rectangular shape of 2.4 ´ 2.8 (cm) and 2 diamond shapes with net mesh size of 5,6 cm and primary hanging ratio of E1 = 0.7 and 0.5. The results showed that rectangular shape bottom wall trap construction was better than those two other constructions. Only 6.78% of snails with l ³ 4.27 cm could escape the rectangular shape bottom wall trap construction. Whereas 41.90% and 17.46% of snail shells with l ³ 4.27 cm could escape from both the diamond mesh bottom wall trap construction. According to selectivity curve, the rectangular shape bottom wall trap construction could retained snails with shells length of l ³ 4.33 cm. The two others retained shells length of l ³ 4.14 cm and l ³ 4.60 cm.